Sensitivity of parasitological test in spleen, bone marrow and lymph node imprints for leishmaniasis diagnosis according to the number of evaluator - de Sousa, Marcus Vinicius C.; Szabó, Matias Pablo Juan; Magalhães, Geórgia Mode; de Queiroz, Rodrigo Pereira; de Castro, Igor Paula; Gabellini, Endrigo Leonel Alves; Medeiros, Alessandra Aparecida; Wilson, Tais Meziara (Brazilian Journal of Veterinary Medicine, 2018)
Visceral Leishmaniasis is considered by the World Health Organization as one of the six priority endemic diseases in the world, once that dogs are natural reservoirs of the parasite. The diagnosis of this disease in dogs is discussed and the purpose of this work was to study the method of parasitological diagnosis of canine visceral leishmaniasis using samples of spleen, bone marrow and lymph node, and to correlate with the clinical signs of the animals and examine the sensitivity parasitological diagnosis performed by one and two observers. There were obtained 59 dogs, by Uberlandia’s Zoonosis Center Control in Minas Gerais State. The animals were clinically examined before the euthanasia and classified as asymptomatic (group 1) (n=6), mildly symptomatic (group 2) (n=34) and symptomatic (group 3) (n=19).Thirty-three (55.93%) were positive, 20 of those (60.60%) were belonged to group 2, 11 of those (33.33%) were to group 3 and 2 (6.06%) were in the group 1. In relation to the organ collected was obtained that 73 (41.24%) were positive samples, 28 (38.35%) from bone marrow, 25 (34.24%) from spleen and 20 (27.39%) from lymph node. When the microscope exam were done by one of the observer, he obtained 13 (3.22%) of positive animals, however the same method evaluated by the second observer this number increased to 33 (55.93%), and this increase was statistically significant. There was no statistical difference between the number of animals distributed among the groups with clinical symptoms, neither the place where the imprints where done. Considering the increase of the sensitivity by the parasitological test, it is recommended that the analyses’ results should be to be obtained by two observers